Türk vergi sisteminde belge düzeni - Şen, Doğan (My University, 2002)
Belge düzeni, Vergi Usul Kanunu ve Vergi Usul Kanunu'nun mükerrer 257. maddesinin verdiği yetkiye istinaden, Maliye Bakanlığı tarafından Vergi Usul Kanunu Genel Tebliğleri ile oluşturulan belgelerin bütünüdür. Türk Vergi Sisteminde yer alan ve çalışmamızın yayınlandığı tarihte yürürlükte olan belgeler tek tek ele alınarak incelenmiştir. Belgelerin temini, muhafazası, ibrazı ve zayi olması, belge düzenine yönelik suç ve cezalar da işlenmek suretiyle belge düzeni konusu bir bütün olarak ele alınmaya çalışılmıştır. Konuların incelenmesi sırasında, Vergi Usul Kanunu Genel Tebliğleri, Maliye Bakanlığı Özelgeleri, Vergi Usul Kanunu İç Genelgeleri ve yargı kararlarından faydalanılmak suretiyle piyasaya yönelik uygulamalara da yer verilmeye özen gösterilmiştir. Bu arada mevcut aksaklıklara değinilmiş ve çözüm önerileri sunulmaya çalışılmıştır. Documentation regulation, is the whole sum of documents formed by The Ministry of Finance with General Bulletins of the Law of Taxation Methods, according to the authorization given by the Law of Taxation Methods and the reiterated item 257 of the foresaid law. The documents which exist in the Turkish Taxation System valid as of the date of our research was made, had been dealt with and studied one by one. Providing, maintenance, presentation and lost of documents, crime and penalty against the document regulations had been tried to be taken under consideration as a whole. While the studies were held, by using the The General Bulletins of the Law of Taxation Methods, the interior-bulletins of the Ministry of Finance, the interior Bulletins of Law of Taxation Methods and court decisions; it was attended to provide actual practical applications. Whilest, was contacted to existing defects and tried to present proposals of solutions.
Keywords: Vergiler_Türkiye